The Personality Structure and Defense Mechanism of the Main Character in Tully Film (2018) - Jasmail, Junalia (English Literature Department, Adab and Humanities Faculty, 2022)
This research is focused on Marlo Moreau as the main character in Tully film (2018). The purpose of this research is to know the psychological condition of the main character in Tully film as seen from her personality structure and also analyze the defense mechanism using Psychoanalysis theory by Sigmund Freud. This research method is a qualitative method and the technique of the research is descriptive analysis to analyze the data with theory that related to the problem of the writer’s research. The data are collected from dialogues in the script and the picture in the film. The finding shows that Marlo Moreau as the 41 years old mother experiences a psychological problem that is the anxiety of reality which also makes her depressed. It appeared since she had a bad experience in her past, which she did not get affection and love from her parents. Moreover, her father had three wives and made Marlo’s condition even worse. This bad experience made her very afraid to accept strangers into her house, so she did all the housework herself and overwhelmed her. Marlo gets pressures that also produce feelings of anxiety. Marlo also has a hallucination by creating a new figure, which she created from her other side. To reduce her anxiety, Marlo has done some defense mechanisms, so that she can get rid of her fear and anxiety.